Do lifestyle habits have an impact on infertility in couples? A systematic review of the topic - Aleksandra Cieślik; Karolina Kosieradzka; Katarzyna Kosecka; Dominik Adamowicz; Patryk Rudziński; Anna Jargieło; Inga Łopuszańska; Justyna Stańczyk; Astrik Meliksetian; Alicja Wosińska (Journal of Education, Health and Sport, 2023)
Background: Infertility is a widespread concern that significantly impacts numerous couples in contemporary times. While the underlying causes of infertility often remain unknown, there is a growing interest in understanding the significant impact that modifiable lifestyle factors can have on its development. Lifestyle factors encompass various habits and ways of life that can be modified to improve overall health, including fertility. It is worth highlighting that these factors are under an individual's control.They play a significant role in determining reproductive health and can positively or negatively influence the ability to conceive.